Description of life cycle and immature stages of Yphthimoides celmis (Godart, [1824]) (Lepidoptera: Nymphalidae: Satyrinae): a contribution to the taxonomic status of the genus - Travesino, Daiana Giselle; Beccacece, Hernán Mario; Zapata, Adriana Inés (Zootaxa, 2023)
This article describes the immature stages of the satyrid butterfly Yphthimoides celmis (Godart) for the first time. Morphology, head and body chaetotaxy, and coloration patterns are compared with those of other Yphthimoides species. Larvae behavioral aspects and oviposition behavior are also documented here. Overwintering larvae are observed for the first time for this genus. The larval stage has four or five instars in non-overwintering while six in overwintering larvae. The average duration of the life cycle is around 82 days for non-overwintering, while it is 227 days for overwintering larvae under laboratory conditions. The increase in instar stages and the development time duration of immature stages in overwintering larvae may be due to climatic conditions in the study area and also a strategy to survive the cold season. Eggs have irregular pentagonal and hexagonal cells. First instar larvae have a dark head capsule and a pattern of reddish stripes along their body, with clubbed body setae. Pupae are short and smooth with a non-uniform brown color, presenting a lighter clypeus and a darker ventral portion in the cremaster. We consider that the morphological information of immature stages can improve further phylogenetic studies.